If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-8x+2(3+4x)=6
We move all terms to the left:
-8x+2(3+4x)-(6)=0
We add all the numbers together, and all the variables
-8x+2(4x+3)-6=0
We multiply parentheses
-8x+8x+6-6=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0
| 6x-3=129 | | 5/10x+3/2=7 | | 17d=16d+19 | | -4(10+3x)-(x-8)=-9 | | x-5-5x=-9 | | 3h+9=51 | | 6x-10=-5x+89 | | 12=7x-4+x | | -6+10g=8g+10 | | -10+8z=6z | | 9+3a-4= | | 4x+6+51=180 | | 9x+17=3x+7=180 | | 8g+1g=30 | | -7(x+5)=91 | | m+7+3m=-2+7m | | -21=3s | | 4x+9=18-(1/2)x | | 1y+3=5 | | 9+3a-4= | | 4x=2x+8.75 | | 17+4x=-3x+6x | | 6x+2=6×3x | | 8x+14=5x | | 8x+12=6x-9 | | 120=-6(5b+6)+6 | | 13g-2.38=14.4g | | 9c-6c+5=23 | | 5600=700a | | (x+9)=x-15 | | 4x+2=16 | | 13+3p+10=29 |